2019
DOI: 10.1111/blar.13018
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Falklands/Malvinas Home: Young People's Everyday Engagements with Geopolitics in Domestic Space

Abstract: This paper draws on recent research examining feminist and everyday geopolitics to focus on the relatively neglected domestic sphere as a space where geopolitical events like the Falklands/Malvinas war are learnt, (re)produced, remembered and contested by young people. It presents qualitative data drawn from interviews with young people from Argentina (Río Gallegos) and the Falkland Islands (Stanley), locations with intimate connections to the 1982 war. It argues that research in domestic environments that eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…When we [young people] learn about our heritage, we do not just learn about it—we bring it to life and turn it into a better future. (Y7)A wide range of studies have investigated how the youth connect with heritage sites, such as their perception and valuing of archaeology (Zaina et al, 2021), heritage sites (McAra, 2021), engagement through museums (Tzibazi, 2013), digital platforms (Selim et al, 2022), social media, and local histories, memory, community, identity, and belonging (Benwell et al, 2020). Existing scholarship has demonstrated that engaging with heritage can positively affect individuals, communities, and societies, through acquiring skills, self-confidence, changing attitudes, creativity, cultural awareness, and cognitive abilities (Wavell et al, 2002).…”
Section: (Re)connecting the Youth With Heritagementioning
confidence: 99%
“…When we [young people] learn about our heritage, we do not just learn about it—we bring it to life and turn it into a better future. (Y7)A wide range of studies have investigated how the youth connect with heritage sites, such as their perception and valuing of archaeology (Zaina et al, 2021), heritage sites (McAra, 2021), engagement through museums (Tzibazi, 2013), digital platforms (Selim et al, 2022), social media, and local histories, memory, community, identity, and belonging (Benwell et al, 2020). Existing scholarship has demonstrated that engaging with heritage can positively affect individuals, communities, and societies, through acquiring skills, self-confidence, changing attitudes, creativity, cultural awareness, and cognitive abilities (Wavell et al, 2002).…”
Section: (Re)connecting the Youth With Heritagementioning
confidence: 99%
“…Collins (2020) then shifts context to highlight how the social embeddedness of young people in the everyday material realities of the home constitutes a knot of mutually influencing entanglements, where individual and wider familial responses to the climate crisis may not always be linear or otherwise straight forward. Through this, she highlights the potential for young people to serve as geopolitical actors through the mundanity of domestic life (Benwell, Gasel, and Núñez 2020;Carter and Woodyer 2020). Finally, she questions the role of young people in 'recruiting' other young people to become climate activists.…”
Section: Interdependent Agenciesmentioning
confidence: 99%